Surface processes during purification of InP quantum dots - Mordvinova, Natalia; Emelin, Pavel; Vinokurov, Alexander; Dorofeev, Sergey; Abakumov, Artem; Kuznetsova, Tatiana (Beilstein Journal of Nanotechnology, 2014)
Recently, a new simple and fast method for the synthesis of InP quantum dots by using phosphine as phosphorous precursor and myristic acid as surface stabilizer was reported. Purification after synthesis is necessary to obtain samples with good optical properties. Two methods of purification were compared and the surface processes which occur during purification were studied. Traditional precipitation with acetone is accompanied by a small increase in photoluminescence. It occurs that during the purification the hydrolysis of the indium precursor takes place, which leads to a better surface passivation. The electrophoretic purification technique does not increase luminescence efficiency but yields very pure quantum dots in only a few minutes. Additionally, the formation of In(OH)3 during the low temperature synthesis was explained. Purification of quantum dots is a very significant part of postsynthetical treatment that determines the properties of the material. But this subject is not sufficiently discussed in the literature. The paper is devoted to the processes that occur at the surface of quantum dots during purification. A new method of purification, electrophoresis, is investigated and described in particular.
Keywords: cadmium-free material; electrophoresis; luminescence; precipitation; purification; quantum dots; semiconductors

(untitled) - Sun, K.; Vasudev, M.; Jung, H.-S.; Yang, J.; Kar, A.; Li, Y.; Reinhardt, K.; Snee, P.; Stroscio, M. A.; Dutta, M. (Microelectron. J., 2009)

(untitled) - Lim, J.; Park, M.; Bae, W. K.; Lee, D.; Lee, S.; Lee, C.; Char, K. (ACS Nano, 2013)

(untitled) - Micic, O. I.; Curtis, C. J.; Jones, K. M.; Sprague, J. R.; Nozik, A. J. (J. Phys. Chem., 1994)

(untitled) - Guzelian, A. A.; Katari, J. E. B.; Kadavanich, A. V.; Banin, U.; Hamad, K.; Juban, E.; Alivisatos, A. P.; Wolters, R. H.; Arnold, C. C.; Heath, J. R. (J. Phys. Chem., 1996)

(untitled) - Mordvinova, N.; Vinokurov, A.; Dorofeev, S.; Kuznetsova, T.; Znamenkov, K. (J. Alloys Compd., 2014)

(untitled) - Vinokurov, A. A.; Dorofeev, S. G.; Znamenkov, K. O.; Panfilova, A. V.; Kuznetsova, T. A. (Mendeleev Commun., 2010)

(untitled) - Kowalczyk, B.; Lagzi, I.; Grzybowski, B. A. (Curr. Opin. Colloid Interface Sci., 2011)

(untitled) - Murray, C. B.; Norris, D. J.; Bawendi, M. G. (J. Am. Chem. Soc., 1993)

Electrophoresis in practice - Westermeier, R. (Wiley-VCH, 2005)

(untitled) - Fu, A.; Micheel, C. M.; Cha, J.; Chang, H.; Yang, H.; Alivisatos, A. P. (J. Am. Chem. Soc., 2004)

Infrared spectroscopy of water - Yukhnevich, G. V. (1973)

Structure Determination Of Organic Compounds - Pretsch, E.; Buellmann, P.; Affolter, C. (Springer, 2000)

(untitled) - Adam, S.; Talapin, D. V.; Borchert, H.; Lobo, A.; McGinley, C.; de Castro, A. R. B.; Haase, M.; Weller, H.; Möller, T. (J. Chem. Phys., 2005)